IL-12-armed oncolytic HSV-2 enhances CAR T cell efficacy against pancreatic cancer in xenografted models - Xu, Chongfeng; Wu, Jian; Liu, Weikang; Zhou, Xiaoya; Liang, Qian; Li, Guoya; Wang, Yang; Liu, Yanliang; Cai, Qiying; Tang, Zilong; Tu, Chunyi; Hu, Han; et al. (Frontiers in Immunology, 2026)
IntroductionChimeric antigen receptor (CAR) T cells show limited efficacy in solid tumors. Oncolytic viruses (OVs), especially those expressing immunomodulatory cytokines like interleukin-12 (IL-12), potentiate to synergize with CAR-T therapy.MethodsWe integrated an IL-12-expressing oncolytic herpes simplex virus type 2 (oHSV-2-IL-12) with mesothelin-targeting SS1-ICOSBBZ-CAR-T to treat Capan-2 pancreatic cancer cells xenografts in B-NDG immunodeficient mice.ResultsSS1-ICOSBBZ-CAR-T alone exhibited partial anti-tumor activity, but could not eradicate established tumors. Intra-tumoral oHSV-2-IL-12 administration potently enhanced CAR-T efficacy, achieving complete and durable tumor elimination even at reduced CAR-T doses. After the initial tumors were fully eliminated by combination therapy, mice were re-challenged by inoculating mesothelin-negative and mesothelin-positive tumor cell lines on the left and right flanks, respectively. In the combination treatment group, mesothelin-positive tumors failed to form new tumors within two weeks after re-challenge, whereas mesothelin-negative tumors grew normally. These findings indicate that oHSV-2-IL-12 combined with CAR-T therapy confers durable, antigen-specific protection against tumor re-challenge. Mechanistically, oHSV-2-IL-12 promoted CAR-T proliferation and persistence in peripheral blood and spleen. IL-12 expression also augmented the direct oncolytic effect of oHSV-2 in immunodeficient hosts.DiscussionThis synergistic approach achieves durable potent tumor clearance with reduced CAR-T doses, offering a transformative strategy against pancreatic cancer and other challenging solid malignancies.